(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2019)
This study is aimed to enrich and strengthen the finding of previous research (1986) titled as “Kotagede between Gates” –a linier traditional settlement set in between “two-gates” in an old Javanese city known as Kotagede. This study discovered six-types of linear patterns associated with road layout that runs East-West where jalan rukunan (‘shared street”) becomes the single access to connect Javanese traditional houses in its linearity pattern. The study also found a pattern change on its linearity caused by a change of ownership, change of kinship and neighborhoods, and the problem of decay (by the age of building) and of damage (by earthquake) of the traditional houses. It is urgent to conserve the Kotagede’s identity in the future, by considering to preserve the existence and the uniqueness of these linear settlements.